PROYEKSI PERTUMBUHAN PEREKONOMIAN PROVINSI LAMPUNG PADA SEKTOR JASA PENDIDIKAN TAHUN 2022 – 2025 - Suradi Suradi Suradi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
One of the sectors that has experienced positive growth in the Lampung Province economy is education services, although currently its contribution is not the largest in the Lampung Province economy. With this positive growth, it becomes interesting to analyze its growth projection. The aim of the research is to make projections of the economic growth of the education services sector in Lampung Province in 2022 – 2025. Descriptive and predictive methods are used in this study. Trend analysis is used to find the best economic growth model (linear, quadratic, cubic, and exponential) which is indicated by the largest termination coefficient (R2) value in the model formed, using Microsoft Excel software. The results showed that the average economic growth in the education services sector in Lampung Province in 2017 - 2022 was 5.56%. Furthermore, the results of the projection analysis for 2022 - 2025 obtained an average economic growth in the education services sector of 23.03%, with the largest growth occurring in 2025 of 55.69%.